1995
DOI: 10.1177/026765839501100303
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between linguistic theory and language processing in SLA

Abstract: This article examines L2 performance in three areas of French morphosyntax by English L1 learners. More particularly, it examines how coindexation as defined within the government-binding framework develops in the L2 grammar. Empirical studies relating the development of two areas of French grammar by English L1 speakers are presented. L2 performance on information questions involving qui and que in which learners have to link the whphrase and its trace in order to establish the syntactic function of the wh -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…We chose to manipulate relative pronoun agreement because a study by Myles (1995) suggested that structural distance is an important variable in the use of gender agreement rules. Myles showed that L2 ability with grammatical gender agreement is correlated with the structural distance (defined in terms of embeddedness) between noun and agreeing element: the greater the structural distance between the agreeing element and the noun, the more difficult the task was.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to manipulate relative pronoun agreement because a study by Myles (1995) suggested that structural distance is an important variable in the use of gender agreement rules. Myles showed that L2 ability with grammatical gender agreement is correlated with the structural distance (defined in terms of embeddedness) between noun and agreeing element: the greater the structural distance between the agreeing element and the noun, the more difficult the task was.…”
Section: Methodsmentioning
confidence: 99%
“…There has been a lot of research on both the comprehension and production of L2 grammatical gender (Andersen, 1984;Rogers, 1984;1987;Finneman, 1992;Shelton, 1996;Myles, 1995;Hawkins, 1998;Dewaele and Véronique, 2000;Franceschina, 2001;2002;White et al, 2004). These studies have shown that L2 gender errors are frequent, that overgeneralization to one form occurs, that accuracy depends on the actual amount of use of the L2 and not on the amount of classroom exposure and that gender agreement seems to be more difficult when the agreeing element is structurally more distant from the noun it has to agree with.…”
Section: Introductionmentioning
confidence: 99%
“…We would also predict less sensitivity in the marked F, P if we were to run a similar test, but that is beyond the scope of the present study. Finally, we concentrated on contiguous N-A concord/discord, following previous studies indicating that longer structural distance between the noun and the modifying adjective results in decreased sensitivity to grammatical gender discord (L2 French: Myles, 1995;L2 Spanish: Keating, 2009; see Almor et al, 2001, for similar findings with subject-verb agreement violations in English monolinguals). For the moving window task, participants read Spanish sentences silently on a computer screen, word-by-word, and answered yes-no comprehension questions (half with yes, half with no target answers) after each sentence.…”
Section: Elmentioning
confidence: 99%
“…Research and anecdotal evidence indicate that lower-proficiency L2/ESL learners rely on semantic/conceptual processing skills along with nonlinguistic processing strategies to compensate for insufficient structure-building skills (Bernhardt, 1986;Bley-Vroman, 1991;Glisan, 1985;Lee & Van Patten, 1995;Pienemann, 1998;White, 1991). In fact some researchers have focused on the development of L2 structure-building skills as the key to fluent sentence processing (e.g., Myles, 1995;Pienemann, 1998). Pienemann (1998) has indicated that most lower-proficiency L2/ESL learners have already acquired a broad range of semantic/conceptual knowledge and processing skills from their L1 language experience, at least for those learning ESL or an L2 after early childhood.…”
Section: L2/esl Sentence Processingmentioning
confidence: 99%